Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share terhadap Hasil Belajar Geografi Siswa Kelas X SMAS Adabiah Padang - Syahfita, Nabila Nissa; Ernawati, Ernawati (ANWARUL, 2024)
Geography is a subject that contains memorized material, so it seems boring. Therefore, the presence of an interesting learning model is very necessary. To overcome this learning process, teachers are required to use creative learning models. One of the creative learning models is the think pair share cooperative learning model. This research aims to 1) analyze learning outcomes in the control class, 2) analyze learning outcomes in the experimental class, 3) analyze the influence of the Think Pair Share Type Cooperative learning model on students' geography learning outcomes. The research method used is quantitative correlational with experimental research type. In this research, the approach used was a quasi-experiment with a pretest-posttest nonequivalent control design research design. The samples taken in this research were 72 students in two classes, namely classes X E1 and X E2. Data collection techniques include observation, pretest and posttest, questionnaires and documentation, and analyzed using statistical tests such as normality test, homogeneity test, linearity test, partial correlation analysis, simple linear regression analysis, hypothesis and N-Gain. The results of the research showed that the posttest score for the experimental class had an average learning outcome of 85 compared to the control class which obtained an average result of 63. This shows that the experimental class experienced a significant increase in learning outcomes compared to the control class which used the conventional model. The N-Gain test results of students in the experimental class got a percentage of 62% (quite effective), while those in the control class got a percentage of 40% (less effective). Simple linear regression analysis also shows that there is an influence of 51% between the use of the Think Pair Share Type Cooperative learning model and student learning outcomes. Thus, it can be concluded that the Think Pair Share Cooperative learning model has a positive influence on students in learning geography at SMAS Adabiah Padang.